Enhancement of the Seismic Performance of Open Ground Storeyed Building using X-bracings. Issue 1 (September 2020) - John, Shemin T; Sahu, Deepak Kumar; Sujeesh, S; Sarkar, Pradip
Abstract: High rise buildings are rapidly increasing in India, and the reason is the unavailability of land. The latest developments in the construction industry improved the utility of available space in productive ways. Perhaps the most recent pattern in the development field is Open Ground Story (OGS) encircled structures, where the ground story is kept open without infill dividers mostly because of points of interest on parking facilities. The ground storey of these buildings are considered as soft and weak, making it most vulnerable to earthquakes, and incorrect structural designing of these buildings will result in catastrophic failure. It is found that the addition of steel bracings significantly improves the seismic performance of OGS buildings in recent years. The motivation of the present study is to focus on the OGS framed buildings with and without steel bracings. In this work, a combination of conservative lateral load resisting systems such as X-bracings and multiplication factor is employed along with moment resisting frame to develop a hybrid system thus by improving the seismic performance of OGS structures.